Politics Women & Well-being - Jeffrey Robin (Oxford University Press, 2001)
The recent history of Kerala proves that a politically active population, in which women have some degree of autonomy, can force the adoption of policies that promote better health and longer life. Kerala achieved the best quality-of-life figures in India during a time when the people of the state had a per capita income below the national average. For 25 years, development experts have pondered a Kerala model of economic development